Systematic realization of non-linear arithmetic functions using hexagonal Field Programmable Analog Array. (August 2022) - Datta, Debanjana; Banerjee, Ayan
Abstract: In spite of being the most popular reconfigurable platform for analog and mixed-mode design implementation, Field-Programmable Analog Array (FPAA) structures are limited to analog filters, amplifiers and communication circuits. Hexagonal FPAA is an established alternative to classical square-lattice FPAA but suitable architectures have not been cultivated much. In this paper, a hexagonal FPAA, implementing different nonlinear functions, eliminating global interconnections, and employing a graph-based mapping algorithm, has been proposed. For communication among the fundamental blocks and reconfiguration, it uses a local interconnection network consisting of central and corner switch blocks. The proposed mapping algorithm uses directed graph representations of fundamental blocks and desired circuits to map the nonlinear functions in the presented FPAA. Weights have been assigned to the graphs and manipulated for efficient placement and routing. All the theoretical predictions have been validated through SPICE simulation using 65 nm CMOS technology. The proposed architecture and mapping algorithm can be extended for large-scale FPAA enriched with automatic placement and routing tools.